Estudio exploratorio para el establecimiento de una metodología para la caracterización geotécnica de material de un tajo, basado en el ensayo de absorción. - Morice-Sandoval, Alejandra (Instituto Tecnológico de Costa Rica, 2010)
The geotechnical characterization of the rocks was determined at Cerro Minas, Santa Ana Quarry. The following study consists on obtaining samples on different terraces of the quarry, in order to generate an assessment and determine, by laboratory and on-the-field (in situ) tests, the rock’s physical and mechanical parameters. The samples for analysis were obtained from the quarry and the rock’s crusher directly. The samples obtained by the explosions and those from the quarry’s finished product, will be evaluated by tests of absorption, specific gravity, abrasion porosity, Ethylene Glycol Immersion, point loads and by the in situ Rebound Hammer test with a sclerometer, in order to establish correlations with statistical validity and to improve the assessment of the materials that they have been working with. After the application of the different tests’ rates, and the determination of the relations between them, it is possible to obtain optimal correlations, according to the theory that sustains them. A sequential program is designed to estimate the absorption test according with different physical and mechanical parameters of the rocks, as well as the application of the stone aggregates according to the results obtained.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela Ingeniería en Construcción, 2010.
Keywords: Mineralogía; Desgaste; Porosidad; Carga; Resistencia